2014
DOI: 10.1371/journal.pone.0089305
|View full text |Cite
|
Sign up to set email alerts
|

Benthic and Pelagic Pathways of Methylmercury Bioaccumulation in Estuarine Food Webs of the Northeast United States

Abstract: Methylmercury (MeHg) is a contaminant of global concern that bioaccumulates and bioamagnifies in marine food webs. Lower trophic level fauna are important conduits of MeHg from sediment and water to estuarine and coastal fish harvested for human consumption. However, the sources and pathways of MeHg to these coastal fisheries are poorly known particularly the potential for transfer of MeHg from the sediment to biotic compartments. Across a broad gradient of human land impacts, we analyzed MeHg concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
100
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 94 publications
13
100
4
Order By: Relevance
“…In addition, accumulated organic matter in bottom sediments is a main factor affecting net MeHg production (39); therefore, inputs of marine mammal excreta and sloughed epidermis may enhance Hg methylation in nearshore sediment. Resuspension of this sediment in the nearshore environment because of wave action, coastal upwelling, storm events, and/or nearshore pinniped activity may also mobilize particulate MeHg to the water column (40), which has been established as a main driver of organic Hg bioaccumulation in estuarine pelagic food webs (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accumulated organic matter in bottom sediments is a main factor affecting net MeHg production (39); therefore, inputs of marine mammal excreta and sloughed epidermis may enhance Hg methylation in nearshore sediment. Resuspension of this sediment in the nearshore environment because of wave action, coastal upwelling, storm events, and/or nearshore pinniped activity may also mobilize particulate MeHg to the water column (40), which has been established as a main driver of organic Hg bioaccumulation in estuarine pelagic food webs (41).…”
Section: Discussionmentioning
confidence: 99%
“…Samples of water, plankton, benthic invertebrates, and fish were collected at both sampling sites. Shaded areas on the map indicate major anthropogenic emission sources (based on Ciesielski et al, 2006) difference between concentrations of elements in organisms inhabiting different ecosystems, as has been reported for instance for methylmercury (MeHg) in benthic and pelagic fauna (Chen et al 2014). The relatively simple pelagic and deepwater benthic food web structures of Lake Baikal (Gurova and Pastukhov 1974;Yoshii 1999;Yoshii et al 1999) make this particular lake a good model system to study the transport of chemical elements in food chains, i.e., their bioavailability in natural waters and their bioaccumulation potential in different trophic levels (Ciesielski et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…[71] reported that deepening the thermocline and oxycline of one lake relative to a reference lake (done by way of pumping at about 15,000 m 3 •day −1 ) increased epilimnetic temperature and oxygen saturation leading to continuing reductions in epilimnetic MeHg and Fish THg, with post-experiment effects lasting for at least one year. Hence, future changes in Fish Hg are also related to climate-induced thermocline inversions, lake-by-lake.…”
Section: Discussionmentioning
confidence: 99%
“…There is much uncertainty about how climate and atmospheric Hg deposition affect Fish THg [2] [3] [4] [5]. In part, this uncertainty is due to large and yet to be quantified land-to-lake and in-lake variations by which Hg uptake by fish increases or decreases.…”
Section: Introductionmentioning
confidence: 99%